Brand Image as Economic Capital: Mediating the Influence of E-WOM and Product Quality on Purchase Intention for Adidas Shoes - Kusumayani, Putu Eka; Telagawathi, Ni Luh Wayan Sayang; Suci, Ni Made (Yayasan Riset dan Pengembangan Intelektual, 2025)
This study aims to examine the mediating role of brand image in the relationship between Electronic Word of Mouth (E-WOM), product quality, and purchase intention for Adidas shoes. Utilizing a causal quantitative research design, the study employs Structural Equation Modeling with Partial Least Squares (SEM-PLS) to test the proposed hypotheses and explain the relationships between variables. The sample was selected through purposive sampling, focusing on undergraduate students at Ganesha University of Education who are familiar with the Adidas brand. The results of the study reveal that E-WOM and product quality both have positive and significant effects on consumers’ purchase intention, while brand image also independently influences purchase intention in a positive and significant manner. Moreover, the findings indicate that E-WOM and product quality each positively and significantly affect brand image. Importantly, brand image is shown to mediate the effects of both E-WOM and product quality on purchase intention, suggesting that a strong brand image serves as a form of economic capital that enhances consumer confidence and drives purchasing decisions. These results underscore the strategic importance of managing digital consumer feedback and maintaining high product standards to strengthen brand positioning and stimulate market demand. Future research could expand on these findings by incorporating variables such as brand loyalty, consumer trust, or the role of social media influencers to better understand purchasing behavior in the digital economy.